Pelatihan Manajemen Usaha untuk Peningkatan Kapasitas Internal Pengusaha Perempuan - Setiawati, Trias; Astuti, Budi; Suhartini; Mulyati, Sri; Nurfauziah (Rahmatan Lil 'Alamin Journal of Community Services, 2024)
Aisyiyah is a social, religious and community organization that was founded in 1917. One of its programs is the economic sector. The Aisyiyah Regional Leadership Economic and Employment Council (MEK PDA) of Bantul Regency has implemented the 'Aisyiyah Entrepreneurial School (SWA) program which aims to provide training to the people of Bantul regarding entrepreneurship so as to build a creative economic atmosphere. Since 2019, these SWA alumni have developed their businesses as a group in various businesses in the community in the Aisyiyah Entrepreneurs Association (IPAS), or currently called the Aisyiyah Merchants and Entrepreneurs Association (ISWARA). This Business Management Training Program aims to increase the internal capacity of ISWARA member female entrepreneurs. It was determined that 30 people (out of a total of 70 active members) were invited to take part in the training series. Business management training is designed as a complete package of material, including: financial management, business promotion in the digital era, teamwork, and strengthening business actuating. The training was carried out by a team of instructors from the UII Community Service Institute (lecturers from the Management Study Program, Faculty of Business and Economics, UII). The results of the training pretest and post-test showed significant progress; namely an average increase of 1.81 (close to a score of 2.0); in addition to motivation and enthusiasm to develop the business further through clever methods, such as neater finances, promotions using digital media, solid teamwork, and business resilience that is developed continuously.